2014
DOI: 10.12741/ebrasilis.v7i2.333
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade de Busca e de Parasitismo de Cotesia flavipes Cameron (Hymenoptera: Braconidae) em Lagartas de Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae)

Abstract: A capacidade do parasitoide de localizar e parasitar o hospedeiro estão diretamente relacionados ao sucesso do controle biológico de pragas. Diante disso, o presente trabalho avaliou o efeito da idade de Cotesia flavipes Cameron na capacidade busca e no parasitismo em lagartas de Diatraea saccharalis (Fabricius) em condições de laboratório. Realizou-se uma liberação de 2000 parasitoides com 24 horas de idade. Foram colocados 40 internódios infestados artificialmente com a broca, na distância de cinco e dez met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…casanarensis . As in other Lepidoptera species [ 27 ], parasitoid larvae emerged from the integument of their hosts searching for a substrate on which to pupate after exiting the Lonomia caterpillar or pupa. We found that Enicospilus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…casanarensis . As in other Lepidoptera species [ 27 ], parasitoid larvae emerged from the integument of their hosts searching for a substrate on which to pupate after exiting the Lonomia caterpillar or pupa. We found that Enicospilus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to describing the immature stages of four species of Lonomia for the first time, we also recorded natural enemies of L. orientocordillera and L. casanarensis. As in other Lepidoptera species [27], parasitoid larvae emerged from the integument of their hosts searching for a substrate on which to pupate after exiting the Lonomia caterpillar or pupa. We found that Enicospilus sp.…”
Section: Plos Onementioning
confidence: 96%
“…For free choice test, each arena held two fragments of sugarcane stalks with 23 cm in length, variety RB 579 infested with one larva of each Diatraea species per stalk, 24 hours before releasing C. flavipes. This procedure provided conditions close to those found in the field and the maximum parasitism capacity (Santos & Mihsfeldt, 2014). Each treatment consisted of 10 replicates, being each one represented by a cage having their ends sealed after the parasitoid female release.…”
Section: Methodsmentioning
confidence: 99%
“…Historically, the most used and viable D. saccharalis management method is the biological control with the use of larval parasitoid Cotesia flavipes Cameron, 1891 (Silva et al, 2014). The efficacy of this parasitoid is proved by a set of samples using visuals and olfactory cues (Silva et al, 2012), search capability in several ages (Santos & Mihsfeldt, 2014), and selectivity (Rossoni et al, 2014), leading to greater susceptibility to Bacillus thuringiensis action (Mahmoud et al, 2011). However, this Braconidae wasp has not been sufficient for D. flavipennella control, being its combined use with entomopathogenic fungi recommended to control this pest (Valente et al, 2014).…”
Section: Introductionmentioning
confidence: 99%